Intermodal Study at Old Gubeng and New Gubeng Railway Stasions Based on Passenger Satisfaction Analysis - Yudhistira M. Agathakarien; Wahju Herijanto (Journal of Civil Engineering, 2024)
With the increasing frequency of trains, more and more people are becoming interested in using them for transportation. However, at Gubeng station, the majority of passengers still prefer to use private vehicles or online transportation instead of public transportation. To evaluate passenger satisfaction with intermodal services at both the new and old Gubeng stations, a performance analysis was conducted. Data analysis uses quadrant analysis with the gap analysis method, the Importance Performance Analysis (IPA) method, the Customer Satisfaction Index (CSI) method, and the Fishbein method. From the results of the analysis, a total of 303 respondents were obtained. In the Gap Analysis method, negative values were obtained for all attributes. The overall service satisfaction index using the Customer Satisfaction Index method obtained a satisfaction index of 0.523 with the criteria "quite satisfied". The overall attitude value of the Fishbein method was 417.335, the criteria for a "neutral" attitude value.